2008
DOI: 10.1152/physiolgenomics.00269.2007
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic capacity-dependent differences in cardiac gene expression

Abstract: Aerobic capacity is a strong predictor of cardiovascular mortality. To determine the relationship between inborn aerobic capacity and cardiac gene expression we examined genome-wide gene expression in hearts of rats artificially selected for high and low running capacity (HCR and LCR, respectively) over 16 generations. The artificial selection of LCR caused accumulation of risk factors of cardiovascular disease similar to the metabolic syndrome seen in human, whereas HCR had markedly better cardiac function. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
41
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 55 publications
6
41
0
Order By: Relevance
“…These findings raise the possibility that impaired microvascular perfusion is a contributing factor to the cardiac phenotype associated with an inherited low capacity for exercise. Previous proteomic and array studies (3,4) suggested that LCR may exhibit a predisposition for LV remodeling, but those studies focused on older animals (30 -50 wk of age). Confirmation of morphological changes specifically on LV histology, protein content, or gene expression using real-time PCR or other semiquantitative approaches was not available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings raise the possibility that impaired microvascular perfusion is a contributing factor to the cardiac phenotype associated with an inherited low capacity for exercise. Previous proteomic and array studies (3,4) suggested that LCR may exhibit a predisposition for LV remodeling, but those studies focused on older animals (30 -50 wk of age). Confirmation of morphological changes specifically on LV histology, protein content, or gene expression using real-time PCR or other semiquantitative approaches was not available.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has now suggested that more mature LCR rats (ϳ30 wk of age) exhibit upregulated cardiac collagen deposition (6). Following enzymatic isolation, cardiomyocytes from older LCR also tend to be shorter and wider than those from their HCR counterparts (4,19). Here we demonstrate that the onset of cardiac fibrosis in the LCR phenotype occurs considerably earlier and is evident already by 12 wk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, elevated amounts of 18:2 n-6, 20:4 n-6, and 22:6 n-3 fatty acids in muscle membranes might have modulated the decreased amounts of free fatty acids and intra-muscular triacylglycerol fatty acids in high-MMR mice (Wone et al 2011). Likewise, a gene expression study of rat heart muscle from Koch and Britton’s (2001) divergent selection experiment on exercise capacity showed that high-capacity runners switched toward fatty acid oxidation metabolism, whereas low-capacity runners switched toward glucose-based metabolism (Bye et al 2008). Hence, one might expect that those fatty acids that are involved in fatty acid metabolism to be present in greater percentages in membranes of cardiac tissues of high-capacity runners compared with low-capacity runners.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, LCR rats exhibit metabolic and cardiovascular phenotypes (i.e., overweight, insulin resistance, elevated blood pressure, and dyslipidemia). Cardiac gene expression profiling indicated the differential expression of numerous genes, especially those related to lipid and glucose metabolism (8). Nonetheless, the functional consequences of differential gene expression in female and male LCR and HCR hearts have not been examined in detail.…”
mentioning
confidence: 99%